Hubungan Antara Lingkungan Kerja Fisik dengan Kesehatan dan Keselamatan Kerja pada Pasukan Kuning di Kota Padang - Harry Theozard Fikri; Rahma Dwi Putri (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2019)
This study aims to see whether there is a relationship between the Physical Work Environment and Occupational Health and Safety in the Yellow Forces in Padang City, with a population of 283 people. The sampling technique used is a simple random sampling technique, namely the technique of taking sample members from the population carried out randomly regardless of the strata that exist within the population. The number of samples in this study were 62 people. from 0.314 to 0.908 and the reliability coefficient is 0.931. While the coefficient of validity on the occupational health and safety scale moves from 0.322 to 0.764 and the reliability coefficient is 0.942. Hypothesis test results show the magnitude of the reliability coefficient of 0.479 with a significant level of p = 0,000 meaning that it can be concluded that there is a significant relationship between the work environment and occupational health and safety, with a positive direction. This means that if the research has a high work environment then work health and safety will also be high. Likewise, if you have a low physical work environment, eating health and safety will also be low. The effective contribution Environment with of the Physical Work Occupational Health and Safety in the Yellow Forces in the City of Padang is 23%.